2022
DOI: 10.1111/jocd.14974
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and tolerability of 40% pyruvic acid peel on acne vulgaris, post acne scar and hyperpigmentation in Indians

Abstract: Introduction: Pyruvic acid in concentration between 40% and 70% is currently been used as a superficial to medium peeling agent for various dermatological indications including acne. However, there is a paucity of its efficacy studies on acne in Asians, particularly in Indian skin.Aim: Our study was aimed at determining the efficacy and tolerability of 40% pyruvic acid on acne, post-acne hyperpigmentation, and scarring. Materials and Methods:A total of 30 patients with active acne, post-acne scarring, and hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The mean reduction rate of this study compared with other reported clinical trials. It is obvious that the treatment of this study is more efficient while costing less time 24–39 …”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…The mean reduction rate of this study compared with other reported clinical trials. It is obvious that the treatment of this study is more efficient while costing less time 24–39 …”
Section: Resultsmentioning
confidence: 93%
“…Compared with 30% SSA, no matter other chemical exfoliators or traditional molecular formation of salicylic acid, the comedone reduction rate was still lower. The reduction rate of 40% pyruvic acid was 38.64% in 24 weeks, that of 25% trichloroacetic acid was 53.91% in 12 weeks, and two lectures reported about the traditional molecular formation of salicylic acid treating AV, whose comedone reduction rate were 56% and 53.71% 24–39 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…And it also improved skin texture. Keisham and colleagues 10 in their study assessed the efficacy and tolerability of 40% pyruvic acid on acne, postacne hyperpigmentation, and scarring. Thirty patients with active acne, postacne scarring, and hyperpigmentation were included.…”
Section: Discussionmentioning
confidence: 99%